Professional Development, a Success Mantra in Business World - Patil, Archana; Somwanshi, Apeksha (SFIMAR Research Review, 2012)
Every coin has two faces; similarly an education degree has two facets - Theory and Practice. We all toss coin at every phase of life, as a student, as a professional and as Employers. Every student joins a business school with confidence to excel in practical world and gain professional knowledge. As the current business environment is ever changing and demanding, Students and Business Schools are required to keep themselves abreast with the latest developments in the business world. Business Cenfers today not only insist for technical knowledge of the individuals being hired but focus more on professional development of the candidates being selected. Studies have proved that there exists a huge gap in the ’Professional Quality’ of individuals developed by the Business Schools and what is expected by the Industries. To bridge this increasing gap of professional capabilities of students and industry expectations, Business Schools today should introduce innovative training methods and create a replica of ’Global village’ within class rooms. Business Schools need to excel not only in Teaching, Learning, and Research but also in overall Professional Development of the students. Professional Development is an active and continuous process of self-appraisal, review and planning of professional and personal development. Activities like Targeted Work, People Management Skills and Soft Skills, Training programs. Corporate Interaction, e-learning. Live Projects are part of professional development, which should be incorporated by Business Schools. This paper makes an attempt to analyze the current imbalance between theory and practice with reference to professional development.